Research commercialization scorecard a model for the evaluation of government-funded R&D slated for commercialization - Hipol, Karen Ann U. author (Technology Management Center, 2009)
The weakest link in the Philippine innovation system is the process of transferring and commercializing the results of research and development, particularly those undertaken by government-funded R&D institutions. The slow pace of technology commercialization is demonstrated by the low number of patents, licenses and revenues generated in the country; particularly when compared to those of our ASEAN neighbors. This study focuses on two factors that contribute to the speed of technological innovation of government funded R&D : the government funds allocated for development projects-- projects that involve proof of concept, prototyping and pilot testing which are necessary prior to commercialization; and the criteria and evaluation procedures used to determine the commercial viability of such projects before they are approved for funding. The study also examines two government institutes that provide funds for development research, the Department of Science and Technology-Technology Innovation for Commercialization Program (TECHNICOM) and the Department of Agriculture Philippine Rice Research Institute (PhilRice). While there is a limited number of government funds specifically allocated for development projects, these funds are not fully liquidated. It could be the lack of a commercial/market mindset and not limited funds that is the leading cause of the dearth of development projects in technology. The sources of development funds, specifically those of DOST-TECHNICOM should be well-marketed to the private sector. They should target to finance development projects that would provide high impact to vital industries, and produce platform technologies that would lead not only to one, but to several new products.